Current Applications of the Three-Dimensional Printing Technology in Neurosurgery: A Review - Łajczak, Paweł Marek; Jóźwik, Kamil; Jaldin Torrico, Cristian (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2024)
Background In the recent years, three-dimensional (3D) printing technology has emerged as a transformative tool, particularly in health care, offering unprecedented possibilities in neurosurgery. This review explores the diverse applications of 3D printing in neurosurgery, assessing its impact on precision, customization, surgical planning, and education.Methods A literature review was conducted using PubMed, Web of Science, Embase, and Scopus, identifying 84 relevant articles. These were categorized into spine applications, neurovascular applications, neuro-oncology applications, neuroendoscopy applications, cranioplasty applications, and modulation/stimulation applications.Results 3D printing applications in spine surgery showcased advancements in guide devices, prosthetics, and neurosurgical planning, with patient-specific models enhancing precision and minimizing complications. Neurovascular applications demonstrated the utility of 3D-printed guide devices in intracranial hemorrhage and enhanced surgical planning for cerebrovascular diseases. Neuro-oncology applications highlighted the role of 3D printing in guide devices for tumor surgery and improved surgical planning through realistic models. Neuroendoscopy applications emphasized the benefits of 3D-printed guide devices, anatomical models, and educational tools. Cranioplasty applications showed promising outcomes in patient-specific implants, addressing biomechanical considerations.Discussion The integration of 3D printing into neurosurgery has significantly advanced precision, customization, and surgical planning. Challenges include standardization, material considerations, and ethical issues. Future directions involve integrating artificial intelligence, multimodal imaging fusion, biofabrication, and global collaboration.Conclusion 3D printing has revolutionized neurosurgery, offering tailored solutions, enhanced surgical planning, and invaluable educational tools. Addressing challenges and exploring future innovations will further solidify the transformative impact of 3D printing in neurosurgical care. This review serves as a comprehensive guide for researchers, clinicians, and policymakers navigating the dynamic landscape of 3D printing in neurosurgery.
Keywords: surgical planning; surgical simulation; 3D printing; additive manufacturing; current technological applications